GAGASAN PEMBAHARUAN SYAH WALIULLAH AD-DIHLAWI DALAM ISLAM - Mubarak, Ahmad Taufik (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2007)
Slxh \\'x[]rnhh xd Dihl."j is a g{ear Islanic relcher in \lughul aud,on$ u lndia llc tned tu g1q t]ri nghr mal to rhe Mong thought and fr{ rhe svstein, iod proposed drc nghr merhod ln dcsrrovng rhe evil wrs. Svatr !;ralilullah rd i)i\hq Eligl.us brckgroNd $ s.a dcep. His rerching conLined dre mzlul,s, bcc^use drc nazhabs .re stil1 in Islm ahosphere. 'this 6 rch unvahealbe trusht of rhc grcar muiaddld ro moslcm in India.